Modeling in situ 4D seismic response for Otway basin CO2 sequestration project - Gendrin, A.; Dahlhaus, L.; Nakanishi, S.; Tcherkashnev, S.; Wisman, P.; Urosevic, Milovan (2018)
Copyright © (2008) by the Society of Exploration Geophysicists All rights reserved. Injection of CO2 into a depleted gas field, Otway basin, Australia, is expected to create very subtle changes in elastic properties of the reservoir. This is a serious challenge for the monitoring program at this site. Here, we perform a series of numerical experiments to evaluate the likelihood of detecting a weak 4D signal caused by CO2 injection. We simulate seismic response changes due to variable near surface conditions. We also take into account the expected ambient noise level. To come to realistic input parameters a detailed analysis of borehole seismic data (several Vertical Seismic Profile, or VSP surveys) is performed. We then analyze the possibility of extracting 4D seismic signatures of CO2 from the simulated low repeatability seismic data.